Comparison of latex and nitrile glove on total bacterial colonisation onclinical students at the Department of Oral and Maxilofacial Surgery Faculty of Dentistry Universitas Sumatera Utara March-May 2018 - Ahyar Riza; Rahmi Syaflida; Abdullah Oes; Arisya Fiqriyah (Journal of Dentomaxillofacial Science, 2019)
Objective: Wearing  glove is one form of self protection from blood, saliva and other body fluids secretion exposure or when health worker’s hand in contact with patient’s mucous membrane during treatment/procedure. The type of glove material could affect its ability to prevent bacterial contamination on hand and the most common type of gloves used are nitrile and latex based material.Material and Methods: This is an experimental research with a post-test only design approach. The sampling technique used is Purposive Sampling. In this study, sample were divided into 2 groups consisting of 18 clinical students wearing latex and nitrile gloves while performing dental extraction on either anterior or posterior tooth.Results: The mean results obtained from latex glove are 88.82±168.56 CFU/ml which is higher than the nitrile group 0.00±0.00 CFU/ml. Based on the Mann-Whitney test results, the p value=0.01<0.05 where there are significant difference between latex and nitrile glove.Conclusion: Based on results of research and data analysis, it can be concluded that there are significant differences in the number of bacterial colonies in latex and nitrile gloves where the use of nitrile gloves are more effective than the latex gloves.